Ancoratus - Epiphanius, Constantiensis 315-403 (The fathers of the church, 2014)
Introduction -- Ancoratus -- Foreword -- Letter from Presbyters of Syedra -- Letter from Palladios -- Ancoratus -- General index -- Index of scriptural allusions and citations